How Multimodal Communication Enhances EFL Students’ Presentation Skills: A Mixed-Methods Study - Rezza Fatwassani; Rudi Hartono; Puji Astuti (Journal of English Language Studies, 2025)
Due to the increasing need for effective communication skills in both academic and professional settings, EFL learners require competencies that extend beyond mere linguistic proficiency. This research investigates the impact of multimodal communication strategies (verbal and non-verbal) on students' presentation skills, focus on five primary modes: linguistic, visual, aural, gestural, and spatial. This study employed a concurrent embedded mixed-methods design involving 17 fourth-semester EFL students at a public university in Semarang, Indonesia. Data were collected using questionnaires, classroom observations, and video recordings. Questionnaire responses (N = 17) were analyzed using Spearman’s correlation (ρ), which is appropriate for ordinal Likert-scale data and does not assume normality or linearity. The analysis revealed significant positive associations between the use of multimodal strategies and improvements in presentation quality, with linguistic (ρ = 0.88) and spatial (ρ = 0.84) strategies showing the strongest effects. All modes contributed positively, and effect sizes are reported with 95% confidence intervals. Qualitative findings corroborated these results, indicating that students who integrated modes exhibited enhanced organization, clarity, and confidence. The non-verbal strategy notably compensated for limited language fluency, thereby enhancing delivery and engagement. The findings underscore the importance of incorporating multimodal training into EFL curricula. Educators should evaluate not only verbal accuracy but also visual, vocal, and spatial components to enhance learners' overall communicative competence.